As transformações do masculino e as masculinidades: uma compreensão junguiana - Madi, Virginia Correia (2020)
The study of the transformation of masculinities is permeated by issues related to changes in the social and cultural spheres, which also passes through issues related to feminism, which, on one hand, allows changes for some women and, on the other, requires that men transform and rethink their social image and deepen the questionings about what it is, after all, to be a man nowadays. The changes achieved in the public sphere also imply the psychic transformation that requires to compose definitions of masculinities that fit in the present time. Directing our attention to men at this moment is relevant, since the entire transformation process involves questionings and a certain degree of sorrow. This work aimed to investigate the possible transformations of masculinities, based on the vision and experience of men aged 30 to 40 years old. It was sought to identify whether the participants recognized these changes, as well as spaces for the transformation of masculinities pointed out by them and the possible effects of these changes on their personal lives and experiences. Therefore, it was adopted a qualitative research methodology with semi-structured interviews. In total, ten participants were interviewed, who met the following inclusion criteria: age range from 30 to 40 years old, heterosexuals, higher education level and average economic and cultural background. The interviews were analyzed by defining thematic groups and sub-themes that characterized the participants' speeches. Then, the thematic groups were described and understood according to Analytical Psychology. Results indicate that for these participants there is an image of man built upon aspects such as virility, power, competition and the silencing of their emotions. This picture has a strong representation in the psyche of these men, directly contributing to the notion of masculinity constructed in their personalities. It was observed the presence of a portion of men who are identifying the transformation of masculinities in society and in their lives, but it was found that these are not everywhere or in all men. This study made it possible to understand that the transformations of masculinities are closely linked to social transformation, due, in part, to the strong influence of women in this process. The perception that masculinity is created and not innate, was one of the perspectives observed in this research and pointed out as fundamental in the search for new forms of expressions of masculinities